1986
DOI: 10.1113/jphysiol.1986.sp016125
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular effects of vasopressin after haemorrhage in anaesthetized rats.

Abstract: SUMMARY1. The cardiovascular effects of an acute haemorrhage (2 % of the body weight)were studied over a 60 min period in three groups of rats: (a) Brattleboro rats with hereditary hypothalamic diabetes insipidus (b.d.i.) lacking circulating vasopressin, (b) control rats of the parent Long Evans (l.e.) strain, and (c) l.e. rats treated with an antagonist of the vascular action of vasopressin.2. Prior to the haemorrhage there were no significant differences between the three groups of rats with respect to mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
5
12
0
2
Order By: Relevance
“…It is also established that microspheres provide an accurate measurement of total renal blood flow (Tsuchiya, Ferrone, Walsh & Frohlich, 1978;Mimran & Casellas, 1979). Although doubts have been expressed over the suitability of microspheres for measuring the distribution of flow within the kidney, owing to the possibility of axial streaming in the interlobular arteries (see Ofstad & Aukland, 1985), streaming can be minimized by the use of 10 psm spheres, as in the present study, rather than the standard 15 ,um spheres (Sabto, Bankir & Griinfeld, 1978); in the rat the entrapment of the smaller spheres in glomeruli is virtually complete (see Al-Omar Azzawi & Shirley, 1983 (Siren et al 1986) and Inactin-anaesthetized (Chapman, Hreash, Laycock & Walter, 1986) rats after severe haemorrhage.…”
Section: Discussionmentioning
confidence: 95%
“…It is also established that microspheres provide an accurate measurement of total renal blood flow (Tsuchiya, Ferrone, Walsh & Frohlich, 1978;Mimran & Casellas, 1979). Although doubts have been expressed over the suitability of microspheres for measuring the distribution of flow within the kidney, owing to the possibility of axial streaming in the interlobular arteries (see Ofstad & Aukland, 1985), streaming can be minimized by the use of 10 psm spheres, as in the present study, rather than the standard 15 ,um spheres (Sabto, Bankir & Griinfeld, 1978); in the rat the entrapment of the smaller spheres in glomeruli is virtually complete (see Al-Omar Azzawi & Shirley, 1983 (Siren et al 1986) and Inactin-anaesthetized (Chapman, Hreash, Laycock & Walter, 1986) rats after severe haemorrhage.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of haemorrhage on blood pressure and its subsequent recovery confirmed that Brattleboro rats are more sensitive to blood volume depletion Johnston et al, 1981;Chapman et al, 1986) and that destruction of peripheral sympathetic nerve endings has a more profound effect on the pressor response to haemorrhage in these animals than in the control Long Evans rats. Pretreatment with 6-hydroxydopamine did appear to be associated with a greater susceptibility to the hypotensive effect of haemorrhage in both strains but the depressor effect was significantly more marked in the Brattleboro DI rats.…”
Section: Discussionmentioning
confidence: 69%
“…Then all rats were anaesthetized with Inactin (I20mgkg-, i.p.) and surgically prepared as described elsewhere (Chapman et al, 1986). Briefly, cannulae were inserted into the bladder, a femoral artery for measurement of heart rate and arterial blood pressure and a femoral vein for infusion of 150 mmolI' NaCl at a rate of 0.5ml 100g-1h1 (and, via an additional cannula in the BDI rats only, 2% glucose solution at a rate determined from the urinary excretion rate to maintain fluid balance).…”
Section: Methodsmentioning
confidence: 99%
“…The neurohypophysial hormone vasopressin has been shown to be important in maintaining arterial blood pressure in specific situations such as haemorrhage (see, for example, Chapman, Hreash, Laycock & Walter, 1986) and water deprivation (see, for example, Andrews & Brenner, 1981). Adult Brattleboro rats with hereditary diabetes insipidus (BDI), lacking circulating vasopressin, and rats of the parent Long-Evans (LE) strain have similar basal arterial pressures whether anaesthetized (Chapman et al 1986) or conscious (Gardiner & Bennett, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Adult Brattleboro rats with hereditary diabetes insipidus (BDI), lacking circulating vasopressin, and rats of the parent Long-Evans (LE) strain have similar basal arterial pressures whether anaesthetized (Chapman et al 1986) or conscious (Gardiner & Bennett, 1985). However we have reported recently that young BDI rats, both anaesthetized and conscious, have a lower mean arterial pressure than age-matched control LE rats (Laycock & Obika, 1988).…”
Section: Introductionmentioning
confidence: 99%